Effects of Menthol Flavor Cigarettes or Total Urinary Menthol on Biomarkers of Nicotine and Carcinogenic Exposure and Behavioral Measures. Issue 9 (20th August 2018) - Ahijevych, Karen; Szalacha, Laura A; Tan, Alai
Abstract: Introduction: The effects of either menthol flavor cigarettes or total urinary menthol on nicotine dependence, biomarkers of addictive and carcinogenic exposure, and behavioral measures may inform differences and similarities of these two approaches. Methods: Stratified recruitment by cigarette (menthol flavor or regular) and race (African American and white) yielded a balanced sample of 136 adult smokers in a 36-hour inpatient protocol. Exposure measures assessed during 24-hour data collection included urinary menthol, total NNAL [4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol], 10 polycyclic aromatic hydrocarbon metabolites, baseline plasma cotinine, plasma nicotine pre- and post-smoking, exhaled carbon monoxide pre- and post-smoking, and cigarette puff volumes. The latter three were measured at four specified timepoints throughout the day. Results: There were no significant differences between menthol flavor and regular cigarette smokers in measures of nicotine dependence, biomarkers of addictive and carcinogenic exposures, or behavioral measures. Significant race × cigarette type interaction effects were found for two biomarkers: plasma nicotine and 3-hydroxyphenanthrene. Total urinary menthol was significantly associated with higher levels of nearly all dependent variables including puff volume, exhaled carbon monoxide, plasma nicotine and cotinine, NNAL, and polycyclic aromatic hydrocarbons. The significant effects of total urinary menthol were sustained after adjusting for menthol flavor and regular cigarette type and other covariates (eg, number of cigarettes per day, baseline cotinine, and baseline nicotine). Conclusions: Urinary menthol is an independent predictive biomarker for nicotine dependence, addictive and carcinogenic exposure, and behaviors. Implications: Comparison of the effects of menthol flavor and total urinary menthol on nicotine dependence, biomarkers of addictive and carcinogenic exposure, and behavioral measures emphasizes the important significant contribution of total urinary menthol concentrations in contrast to no significant associations by dichotomous cigarette type with these biomarkers.